Epicyclic gearbox fault detection by Instantaneous Circular Pitch Cycle Map. (15th April 2019) - Dziedziech, Kajetan; Jablonski, Adam; Dworakowski, Ziemowit
Highlights: ICPCM can be of a power or peak type, and these can lead to different observations. ICPCM is an extension of TSA, which enable to analyse variations with respect to time. ICPCM is calculated for different orders, presenting new features of analysed signal. Angle domain processing is done with different RRO, making the analysis easier. ICPCM does not suffer the frequency resolution problems and uses short data sets. Abstract: The paper introduces the concept of Instantaneous Circular Pitch Cycle Map (ICPCM) as a tool for analysis and diagnosis of modulation signatures in vibrations generated by Epicyclic Gearbox (EGs). The method is based on the representation of a vibration signal as a 3-D map illustrating selected signal properties. Within the method, a novel concept of a Resampling Relative Order (RRO) is introduced. The paper illustrates how the ICPCM might serve as an auxiliary tool for proper interpretation of spectra, envelope spectra, and time-synchronous averaged representations. The idea of the method is presented on a simulated signal, while its practical performance is illustrated on a real signal from a multi-stage EG.